Multi-objective optimization for the sustainable planning of yam cultivation and distribution in the Colombian Caribbean - Vergara Rodríguez, César José; Mendoza-Ortega, Gean Pablo; Mármol Barriosnuevo, Mayerlis; Díaz Sierra, Mayerly (Frontiers in Sustainability, 2025)
Yam agri-food chains in the department of Sucre experience logistical losses exceeding 30% in certain stages, compromising both economic performance and social sustainability. To address these inefficiencies, this study develops a multi-objective optimization model that supports strategic planning by integrating profit maximization and loss minimization criteria. The model was implemented in GAMS (version 49.6.1) using the CPLEX 12.8 solver and solved through the AUGMECON method. The resulting Pareto-efficient solutions were evaluated using slope analysis and the TOPSIS multi-criteria decision method. The results reveal a clear trade-off between economic benefit and loss reduction, identifying Solution 14 as the most balanced configuration, achieving approximately USD 4.241 million in profits and 683,818 kg in losses. These findings highlight the potential of combining multi-objective modeling and decision-support analysis to promote more sustainable planning in agri-food chains. The proposed strategies—focused on loss reduction, supplier diversification, and optimized sowing planning—offer practical guidance for improving territorial sustainability and decision-making in regional agricultural systems.